Decoupling the Impacts of Engineering Defects and Band Gap Alignment Mechanism on the Catalytic Performance of Holey 2D CeO2−x‐Based Heterojunctions. (3rd July 2021) - Zheng, Xiaoran; Mofarah, Sajjad S.; Cazorla, Claudio; Daiyan, Rahman; Esmailpour, Ali Asghar; Scott, Jason; Yao, Yin; Lim, Sean; Wong, Vienna; Chen, Ewing Y.; Arandiyan, Hamidreza; Koshy, Pramod; et al.
Abstract: Critical catalysis studies often lack elucidation of the mechanistic role of defect equilibria in solid solubility and charge compensation. This approach is applied to interpret the physicochemical properties and catalytic performance of a free‐standing 2D–3D CeO2− x scaffold, which is comprised of holey 2D nanosheets, and its heterojunctions with MoO3− x and RuO2 . The band gap alignment and structural defects are engineered using density functional theory (DFT) simulations and atomic characterization. Further, the heterojunctions are used in hydrogen evolution reaction (HER) and catalytic ozonation applications, and the impacts of the metal oxide heteroatoms are analyzed. A key outcome is that the principal regulator of the ozonation performance is not oxygen vacancies but the concentration of Ce 3+ and Ce vacancies. Cation vacancy defects are measured to be as high as 8.1 at% for Ru‐CeO2− x . The homogeneous distribution of chemisorbed, Mo‐oxide, heterojunction nanoparticles on the CeO2− x holey nanosheets facilitates intervalence charge transfer, resulting in the dominant effect and resultant ≈50% decrease in overpotential for HER. The heterojunctions are tested for aqueous‐catalytic ozonation of salicylic acid, revealing excellent catalytic performance from Mo doping despite the adverse impact of Ce vacancies. The present study highlights the use of defect engineering to leverage experimental and DFT results for band alignment. Abstract : Synthesis, density functional theory simulations, and physicochemical atomic characterization of 3D CeO2− x ‐based heterojunctions comprised of holey 2D nanosheets are presented to showcase the engineering of band gap alignment and structural defects for outstanding catalytic performance. The formation of defects of varying dimensionalities (1D, 2D, 3D) occurs from adsorption, interstitial solid solubility, intrinsic oxygen vacancies ( V O ), and charge compensation.